Digital divide among college teachers: Assessing faculty’s information and communication technology access - Venkateswar Meher; Tushar Kanta Sahu (S&Co Publishing, 2024)
The study highlighted the digital divide as not only a technological divide but also a socio-cultural divide. In the present study, we examined the digital divide of college teachers through ICT access by taking demographic variables like gender, locality, age, teaching experience, academic streams, and type of colleges. We selected approximately 158 college teachers from the Bargarh district of Odisha, covering government, aided, and private colleges, as participants for the study. We collected primary data on ICT access among college teachers to study the digital divide. The digital divide among college teachers was examined with reference to ICT access, physical access, motivational access, skill access, and usage access. In the present study, about 43.67% of teachers had high ICT access, while about 56.33% of teachers had low ICT access. Physical access and usage access of urban college teachers were significantly higher than those of rural teachers. ICT access, physical access, skill access, and usage access among college teachers below the average age were significantly higher than among teachers above the average age. ICT access and skill access of college teachers with below-average teaching experience were significantly higher than the teachers having above-average teaching experience. College teachers in commerce streams had higher physical access to ICT. ICT access among private college teachers was significantly higher as compared to government and aided colleges. From the results, it can be inferred that demographic variables were responsible for the digital divide among college teachers to some extent.